Lack of genotoxicity in vivo for food color additive Tartrazine. (July 2017) - Bastaki, Maria; Farrell, Thomas; Bhusari, Sachin; Pant, Kamala; Kulkarni, Rohan
Abstract: Tartrazine is approved as a food color additive internationally with INS number 102, in the United States as food color subject to batch certification "Food, Drug, and Cosmetic" (FD&C) Yellow No. 5, and in Europe as food color additive with E number 102. In their evaluation of the color (2013), the European Food Safety Authority (EFSA) expressed concerns of potential genotoxicity, based primarily on one genotoxicity study that was not conducted according to Guidelines. The present in vivo genotoxicity study was conducted according to OECD Guidelines in response to EFSA's request for additional data. The animal species and strain, and the tissues examined were selected specifically to address the previously reported findings. The results of this study show clear absence of genotoxic activity for Tartrazine, in the bone marrow micronucleus assay and the Comet assay in the liver, stomach, and colon. These data addressed EFSA's concerns for genotoxicity. The Joint WHO/FAO Committee on Food Additives (JECFA) (2016) also reviewed these data and concluded that there is no genotoxicity concern for Tartrazine. Negative findings in parallel genotoxicity studies on Allura Red AC and Ponceau 4R (published separately) are consistent with lack of genotoxicity for azo dyes used as food colors. Highlights: The genotoxicity of Tartrazine was determined in a GLP- and OECD Guideline-compliant study in mice. Tartrazine was negative for genotoxicity in the bone marrow micronucleus assay. Tartrazine was negative for genotoxicity in the Comet assay in the liver, stomach, and colon. The study was conducted in response to request for additional information by the European Food Safety Authority (EFSA).